The implicit relation of psychology and law : women and syndrome evidence - Raitt, Fiona E. (Routledge, 2000)
From a feminist perspective, the authors critically review the current use of psychology in law and identify a powerful collusion between the two fields which works actively against the interests of women. They provide support for their argument in such areas as child abuse, domestic violence, rape and abortion. This groundbreaking international text draws on both research findings and case material from various countries including Australia, New Zealand, Canada and South Africa as well as the USA and Great Britain. The Implicit Relation of Psychology and Law brings an i.